Influence of Investment on Economic Growth, Human Development, Poverty and Unemployment in Bangka Belitung Island Province in the 2018–2023 Period (Jurnal Bina Praja, 2025)
Investment is one of the key factors that affect economic dynamics. This research focuses on the Bangka Belitung Islands Province, specifically its investment in the tin and non-tin sectors, as the largest tin-producing area in the world. Investment is an important component in capital formation; investment has great potential to spur economic growth, improve people's quality of life, and reduce social problems such as poverty and unemployment. The aim of this research is to determine the effect of investment in the tin and non-tin sectors on economic growth, the Human Development Index, poverty levels, and unemployment rates in the Bangka Belitung Islands Province from 2018 to 2023. Associative quantitative research type, with multiple regression analysis tools. The research results indicate that investment in the tin sector has a positive impact, while investment in the non-tin sector has a negative impact on economic growth; however, this effect is not statistically significant. Tin sector investment and non-tin sector investment have a negative impact on the Human Development Index, although it is not statistically significant. Tin sector investment has a positive and significant effect, while non-tin sector investment has a negative effect on poverty levels, but this effect is not statistically significant. Investment in the tin sector and non-tin investment have a negative effect on the unemployment rate, but this effect is not significant.  The conclusion from research over the last six years is that investment conditions have decreased significantly. This decline began with the COVID-19 incident in 2019, and that had an impact on economic and social development. The solution needs to be more proactive in both the government and private sectors to increase investment from investors, both domestic and foreign. Apart from that, there is a need to set a quality investment strategy so that the investment can be beneficial for increasing socio-economic development, especially in the Bangka Belitung Islands Province.
Keywords: Investment; Economic Growth; Human Development; Poverty; Unemployment